CLINICAL FEATURES OF COVID-19 AND ASSESSMENT OF THE HEALTH STATUS OF CHILDREN IN UFA WHO HAVE SUFFERED A NEW CORONAVIRUS INFECTION IN OUTPATIENT CARE - Тихонова, Регина Зинуровна; Кучина, Екатерина Серимжановна; Яковлева, Людмила Викторовна (Mother and Baby in Kuzbass, 2024)
The aim – to identify the clinical features of the course of COVID-19 and assess the health status of children who have had a new coronavirus infection during the last 6 months after infection.Materials and methods. On the basis of the «Children's Clinic № 5» in Ufa and «Children's Clinic № 3» in Ufa, 183 children aged 0 to 17 years who had COVID-19 from January 2022 to April 2023 were examined.Results. The new coronavirus infection was more often recorded in boys – in 61.2 % of cases, and in boys aged from 1 to 7 years – in 51.4 % of cases. The presence of a premorbid background was detected in 82,5 % of children; diseases of the nervous system prevailed – 31.1 % of cases and congenital heart anomalies – 27.8 % of cases. The leading clinical manifestations of COVID-19 were: fever – in 73.8 % of cases, weakness/lethargy and loss of appetite – in 65 % and 63.9 % of cases, cough – in 53.6 % of cases. The main manifestations of post-Covid syndrome: neurocognitive – in 51.4 % of children, pain in the heart area – in 43.2 % of children, loss of appetite – in 44.8 % of children. Mild anemia was recorded in 33.3 % of children. 70.5 % of children had pathological changes in the electrocardiogram: disturbances in repolarization processes – in 40.3 % of cases, sinus tachycardia – in 31 % of cases, atrioventricular block – in 10.8 % of cases.Conclutions. The leading clinical syndrome of post-Covid symptoms was asthenia, cardiac symptoms in the form of impaired repolarization processes, conduction, sinus tachycardia, mild anemia and a decrease in the level of resistance to acute respiratory diseases. It is necessary to carry out a minimum amount of research (CBC, OAM, ECG) in order to subsequently prescribe an individual program of treatment, preventive, rehabilitation measures and dynamic monitoring of the child’s health after a coronavirus infection.
Keywords: children; COVID-19; post-Covid syndrome; clinical and anamnestic features; asthenia; cardiac symptoms; anemia